Physicochemical and Sensory Evaluation of Purple Sweet Potato and Jackfruit Seed Flour-Based Food Bars - Kumalasari, Ika Dyah; Yensi, Indri (Department of Agro-industrial Technology, University of Brawijaya, 2024)
AbstractThis study aimed to determine food bars' physical, chemical, and organoleptic characteristics based on purple sweet potato flour and jackfruit seed flour. This study used a completely randomized design (CRD). The ratio of purple sweet potato flour and jackfruit seed flour used was F1 (20%: 80%), F2 (40%: 60%), F3 (50%: 50%), F4 (60%: 40%), and F5 (80%: 20%). The parameters tested were physical parameters (texture (hardness) and color), chemical parameters (water content, ash content, carbohydrates content, protein content, fat content, fiber content, total sugar content, and antioxidant activity), and organoleptic analysis (aroma, taste, color, texture, aftertaste, and overall). Data analysis used the ANOVA test with a 5% significance level and Duncan's Multiple Range Test. The analysis showed that food bars made from purple sweet potato flour and jackfruit seed flour in each formulation significantly affected physical, chemical, and organoleptic properties. The study results showed that along with the increasing percentage of jackfruit seed flour and decreasing percentage of purple sweet potato, the water content, ash content, protein content, and antioxidant activity increased in food bars. However, the fat content, carbohydrate content, crude fiber content, and total sugar content decreased.Keywords: food bar, jackfruit seed flour, organoleptic, physicochemical, purple sweet potato flour AbstrakPenelitian ini bertujuan untuk mengetahui karakteristik fisik, kimia dan organoleptik food bar berbasis tepung ubi jalar ungu dan tepung biji nangka. Penelitian ini menggunakan Rancangan Acak lengkap (RAL). Perbandingan tepung ubi jalar ungu dan tepung biji nangka yang digunakan adalah F1 (20%:80%), F2 (40%:60%), F3 (50%:50%), F4 (60%:40%), dan F5 (80%:20%). Parameter yang diuji adalah parameter fisik (tekstur (hardness) dan warna), parameter kimia (kadar air, kadar abu, kadar karbohidrat, kadar protein, kadar lemak, kadar serat, kadar gula total, dan aktivitas antioksidan) dan analisis organoleptik (aroma, rasa, warna, tekstur, aftertaste, dan keseluruhan). Analisis data menggunakan uji ANOVA dengan taraf signifikansi 5% dengan uji lanjut Duncan. Hasil analisis menunjukkan bahwa food bar tepung ubi jalar ungu dan tepung biji nangka pada setiap formulasi memberikan pengaruh secara signifikan pada sifat fisik, kimia, dan organoleptik. Hasil penelitian menunjukan seiring dengan semakin tinggi persentase tepung biji nangka dan semakin rendah persentase tepung ubi jalar ungu, kadar air, kadar abu, kadar protein, dan aktivitas antioksidan meningkat. Namun, kadar lemak, kadar karbohidrat, kadar serat kasar, dan kadar gula total menurun.Kata kunci: fisikokimia, food bar, organoleptik, tepung biji nangka, tepung ubi jalar ungu